Extraction of natural hydroxyapatite for biomedical applications—a review - Abdulah, Hasan Zuhudi; Hussin, Mohamed Saiful Firdaus; Idris, Maizlinda Izwana; Abdul Wahap, Mohd Arizam (Elsevier Ltd, 2022)
Hydroxyapatite has recently played a crucial role in the sustainable development of biomedical applications. Publications related to hydroxyapatite as filler for biopolymers have exhibited an increasing trend due to the expanding research output. Based on the latest publications, the authors reviewed the research trends regarding hydroxyapatite use in biomedical applications. Analysis of the Scopus database using the keywords ‘hydroxyapatite” and “biomedical applications” determined that 1,714 papers were produced between 2012 and 2021. The number of publications related to these keywords more than doubled between 2012 (99) and 2021 (247). The hydrothermal method, solid-state reactions, the sol-gel process, emulsion, micro-emulsion, and mostly chemical precipitation were used to produce synthetic hydroxyapatite. Meanwhile, calcination, alkaline hydrolysis, precipitation, hydrothermal, and a combination of these techniques were used in producing natural hydroxyapatite. Studies in the current literature reveal that shell-based animal sources have been frequently used as hydroxyapatite resources during investigations concerning biomedical applications, while calcination was the extraction method most often applied. Essential trace elements of fish bone, oyster shell, and eggshell were also found in hydroxyapatite powder. Abalone mussel shell and eggshell showed Ca/P ratios closer to the stoichiometric ratio due to the use of effective extraction methods such as manipulating aging time or stirring process parameters. This review should greatly assist by offering scientific insights to support all the recommended future research works, not only that associated with biomedical applications.